Algorithms and Models for the Web-Graph 7th International Workshop, WAW 2010, Stanford, CA, USA, December 13-14, 2010. Proceedings - Kumar, Ravi.; Sivakumar, Dandapani; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 7th International Workshop on Algorithms and Models for the Web-Graph, WAW 2010, held in Stanford, CA, USA, in December 2010, which was co-located with the 6th International Workshop on Internet and Network Economics (WINE 2010). The 13 revised full papers and the invited paper presented were carefully reviewed and selected from 19 submissions.
Keywords: Computer science; Computer software; Database management; Data mining; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Algorithm Analysis and Problem Complexity; Database Management; Data Mining and Knowledge Discovery